How To Get a Girl Pregnant: An Autoethnography of Chicana Butch Reproduction - Pendleton Jiménez, Karleen (Journal of the Motherhood Initiative for Research and Community Involvement, 2015)
“How To Get a Girl Pregnant” is a memoir documenting a butch lesbian’s questto become pregnant. This essay includes a short discussion of the text as autoethnographycoupled with an excerpt from the memoir. Throughout the memoir theauthor attempts to deconstruct normative conceptions of fertility and pregnancy.She explores the influence of gender and ethnic identities (butch and Chicana) onher experience in a fertility clinic, and on the lived conditions of reproduction. Herbody, at the intersection of gender, sexuality and ethnicity, produces knowledge forscholarly inquiry. The memoir was constructed through fieldnotes and reflectivejournaling. Her observations and analyses reveal insights into the sensibilities andvalues of fertility clinics, as well as those of the communities that have shaped her. Sheconsiders questions such as: How do heterosexist practices in fertility treatments leadto misunderstandings with lgbt clients? How does gender socialization influence abutch’s experience of fertility? How does one’s sense of individual power and desireoperate through reproduction treatments?